2020
DOI: 10.1051/0004-6361/201936553
|View full text |Cite
|
Sign up to set email alerts
|

The long-lived Type IIn SN 2015da: Infrared echoes and strong interaction within an extended massive shell

Abstract: We report the results of the first ∼ 4 years of spectroscopic and photometric monitoring of the Type IIn supernova SN 2015da (aka PSN J13522411+3941286, or iPTF16tu). The supernova exploded in the nearby spiral galaxy NGC 5337, in a relatively highly extinguished environment. SN 2015da shows prominent Balmer lines in emission with narrow components at all times and a slow rise to maximum. In addition, early observations performed by amateur astronomers give a very well-constrained explosion epoch. The observab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 129 publications
4
47
0
Order By: Relevance
“…Lorentzian) Balmer lines. This similarity persists for most events [5,4,84,13,62] throughout their evolution, as the continuum cools and the equivalent widths of the lines increase. SN2006gy and CSS121015 are exceptions.…”
Section: Ruling Out a Tidal Disruption Eventmentioning
confidence: 66%
See 3 more Smart Citations
“…Lorentzian) Balmer lines. This similarity persists for most events [5,4,84,13,62] throughout their evolution, as the continuum cools and the equivalent widths of the lines increase. SN2006gy and CSS121015 are exceptions.…”
Section: Ruling Out a Tidal Disruption Eventmentioning
confidence: 66%
“…We also note that we do not have near-infrared data to look for dust formation, common in interacting SNe at late times [65,66]. Any late-time infrared excess, as seen [65,14,62] in the spectroscopically similar and slowly-evolving SLSNe IIn SN2010jl and SN2015da, would also increase the total E rad further. Thus the integrated observed E rad = 5 × 10 51 erg is a conservative lower limit on the total energy.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Notable exceptions are the most luminous and long-lasting Type IIn SNe such as SN 2010jl (Andrews et al 2011;Fox et al 2013;Fransson et al 2014), SN 2015da (Tartaglia et al 2020), and SN 1988Z (Aretxaga et al 1999, which have been observed to emit >10 50 erg and display prominent hydrogen emission lines from the interaction of the SN ejecta with H-rich circumstellar gas. Furthermore, many Type IIn SNe have been observed to show prominent long-lasting mid-IR emission, most likely due to reradiation by pre-existing dust (Fox et al 2011).…”
Section: Supernovamentioning
confidence: 99%